Recent Research on the Megilloth (Song of Songs, Ruth, Lamentations, Ecclesiastes, Esther). (June 2016) - Erickson, Amy; Davis, Andrew R.
Until recently, study of the Megilloth as a coherent canonical grouping has been minimal. On the whole, the lateness and fluidity of the collection within the Jewish canon has negated its value for biblical scholars, who have long preferred texts and categories thought to be 'early' or 'original'. The state of the field has begun to shift, however, as scholars are giving more attention to connections between individual books of the Megilloth and the coherence of the collection as a whole. This new interest coincides with the growing recognition among scholars that the later (re)uses of a biblical text are constitutive of its interpretation; thus the lateness of the Megilloth (if the collection really is late) does not preclude interpretation but shapes it. Recent studies in the Megilloth as a coherent collection include canon-historical approaches, which trace the formation of the Megilloth within the Jewish canon; intertextual approaches, which focus on allusions to earlier biblical traditions and on literary connections within the five scrolls; and theological approaches, which adopt a synchronic method that puts the Megilloth in dialogue with contemporary theological discourse.